Assessment of the Ability to Identify Fake News Among Out-of-School Youth and Adults: Penilaian Kemampuan Mengidentifikasi Berita Palsu pada Pemuda Putus Sekolah dan Orang Dewasa - Lutog, Marevic Jean (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
Literacy skills to detect disinformation. With the proliferation of fake news in various media platforms, it is relevant to recognize the ability of individuals to comprehend various instances of manipulated information. This study encompasses skills on distinguishing fact from opinion, recognizing bias, analyzing visuals, and evaluating sources. The respondents were 100 randomly chosen out-of-school youth and adults enrolled in the Alternative Learning System of the City of Mati. Measuring this competence in ALS learners is essential considering the unequal access to formal education and the lack of exposure to structured digital literacy curricula, which potentially places them at a higher risk of disinformation. By utilizing a descriptive quantitative method, the respondents answered the Fake News Identification Ability Test which consists of a 40-item text and visual-based scenario contextualized in the Philippine setting. It was revealed that these indicators attained a high level of competence, with the exception for evaluating sources which was found to be on a low level. Although the over-all results are affirmative, it is advisable to have further learning and development on detecting fake news. Strengthening these skills will benefit the out-of-school youth and adults and would create a positive contribution to the community.